Factors Affecting Small and Medium Enterprises Success: An Exploratory Study - Jebna, Abdul Karim Kanaan; Baharudin, Ahmad Suhaimi (Penerbit Universiti Teknologi Malaysia, 2013)
Small and medium enterprises (SMEs) are the main contributor toward prospering the Malaysian economy [1]. Despite the fact that Malaysia is a fast growing economy in South-East Asia, death of SMEs is unavoidable. An exploratory study was conducted to investigate the factors that have an impact on business performance and success in Malaysia. Interviews with SMEs from different industries were conducted. Several factors were found to contribute to the success of business. The factors are classified into financial and non-financial determinants. These factors include customer satisfaction, service quality, experience, business expansion, competitor orientation, solving problems, cash flow, and the amount of sales and revenue. Building on these interviews, a discussion and conclusion have been provided.